Course-, dose-, and stage-dependent toxic effects of prenatal dexamethasone exposure on fetal articular cartilage development. (April 2018) - Chen, Ze; Zhao, Zhe; Li, Yunzepeng; Zhang, Xingyu; Li, Bin; Chen, Liaobin; Wang, Hui
Highlights: Multiple courses of PDE had stronger toxic effects on fetal articular cartilage. PDE at dose above 0.8 mg/kg d induced stronger developmental toxicity. PDE at the early stage of pregnancy induced severer articular cartilage dysplasia. Dexamethasone down-regulated the TGFβ-Smad2/3-Sox9 signaling pathway. Abstract: Dexamethasone, a synthetic long-acting glucocorticoid, is routinely used for treating mothers at risk for preterm delivery. However, intrauterine overexposure to glucocorticoids induces low birth weight and cartilage dysplasia in offspring. Also, the "critical window" and safe dose of this treatment are largely unknown. This study investigated the course-, dose-, and stage-dependent toxic effects and the possible mechanisms of prenatal dexamethasone exposure (PDE) on fetal development and articular cartilage development. Pregnant mice (C57BL/6) received subcutaneous injection of dexamethasone (0.8 mg/kg d) once on gestational day (GD) 15 or once a day from GD 15 to 17, or received various doses of dexamethasone (0, 0.2, 0.8, and 1.2 mg/kg d) on GD 15–17, or received dexamethasone (0.8 mg/kg d) at early stage (GD 12–14) or late stage of pregnancy (GD 15–17). Offspring's knee joints were harvested at birth for morphological analyses and detection of gene expression. Repeated PDE significantly suppressed fetal and articular cartilage development, which were characterized by decreased body weight and body length, coarse articular cartilage surfaces, and reduced gene and protein expression of Col2a1 and aggrecan. For those newborns treated with repeated PDE at different doses, the toxic effects on fetal and articular cartilage development were observed at doses of 0.8 and 1.2 mg/kg d, whereas no obvious toxic effects were observed at the dose of 0.2 mg/kg d. Moreover, PDE at 0.8 mg/kg d during the early embryonic stage induced stronger toxic effects on fetal and articular cartilage development, compared with PDE during the late embryonic stage. Detection of gene expression showed that the TGFβ signaling pathway in the articular cartilage was down-regulated after PDE. Taken together, PDE induces fetal developmental toxicity and articular cartilage developmental toxicity in a course-, dose-, and stage-dependent manner.